SOME COVERING PROPERTIES USING MAXIMAL OPEN COVERS - Bagchi, Kallol Bhandhu (Matematichki Bilten, 2021)
The aim of this article is to study some covering properties using maximal open covers in topological spaces. We see that in a \(m\)-Lindelöf topological space each uncountable subset has a complete \(m\)-accumulation point as well as \(m\)-accumulation point. Furthermore we see that a Hausdorff \(m\)-paracompact topological space is minimal \(c\)-normal.